Beyond EU Law Heroes: Unleashing Strategic Litigation as a Form of Participation in the Union’s Democratic Life - Alberto Alemanno (German Law Journal)
This Article discusses the emerging strategic litigation practice in the European Union through the lens of participatory democracy. After situating such a practice both historically and conceptually within the specificities of the EU legal order, it explores whether and the extent to which strategic litigation, understood as an additional form of participation in the Union’s democratic life, may contribute to EU participatory democracy and under which conditions. It unveils that while strategic litigation carries the potential to enhance democratic participation in the EU, it also risks—due to limited judicial literacy and unequal access to justice—empowering those already powerful. For strategic litigation to unleash its democratic potential at scale, EU courts must—as required by the “Provisions on Democratic Principles” of the Treaty of Lisbon—ensure a participatory enabling environment capable of proactively catalyzing and facilitating the ability of ordinary citizens—as well as diffuse, under-resourced and traditionally overlooked groups—to be better able to contribute to the Union’s democratic life. Ultimately, no legal order worth of its name should rely on the heroism of its citizens and residents to keep its legal system in check.